The Relevance of Rights and Duties of Husband and Wife in Positive Law and Tafsir Al-Ahkam on Q.S. Al-Baqarah: 228: Relevansi Hak dan Kewajiban Suami Istri dalam Hukum Positif dan Tafsir Al-Ahkam pada Q.S. Al-Baqarah: 228 (Takwil: Journal of Quran and Hadith Studies, 2024)
Islam is a religion revealed to the Prophet Muhammad SAW. The revelation regulates all aspects of life in this world, both organizing human relationships to the creator and relationships between fellow humans, one of which is marriage or marriage. Every human being must have the desire to get married and build a harmonious household because marriage is one of the sunatullah. However, not a few households are unhappy due to the lack of knowledge of married couples about how to form a household that is sakinah, mawadah wa rahmah according to the instructions taught in the Quran. In addition, many families do not run harmoniously due to the lack of knowledge of the male and female towards their respective rights and responsibilities towards their spouses. The purpose of this study is to analyze the relevance of Quranic verses on the rights and duties of husband and wife based on the principles of tafsir Al-Ahkam, This study uses a qualitative approach with the method of literature analysis and literature study, The type of data in this study will be collected from various sources, including books, scientific journals, laws and regulations, and other related documents. The results of this study show that the verse of Al-Quran surat Al-Baqarah verse 228 has relevance and is appropriate to the rights and duties of husband and wife in the family household.